2006
DOI: 10.1037/1528-3542.6.1.156
|View full text |Cite
|
Sign up to set email alerts
|

When people fall from grace: Reconsidering the role of envy in schadenfreude.

Abstract: Previous research yielded conflicting results concerning the role of envy in predicting Schadenfreude (pleasure at another's misfortune). Some studies showed that envy predicts Schadenfreude, whereas others did not. Results of the present research reconcile these opposing findings, by showing that envy is a predictor of Schadenfreude when the target is similar to the observer in terms of gender. These results suggest that envy predicts Schadenfreude when people are confronted with the misfortune of a relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
154
5
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 24 publications
8
154
5
14
Order By: Relevance
“…Research on schadenfreude has shown this malicious joy to be evoked by the downfall of high achievers, especially when they are envied or resented (Feather & Sherman, 2002;Smith et al, 1996;Van Dijk, Ouwerkerk, Goslinga, Nieweg, & Gallucci, 2006). But are high achievers always an easy prey for schadenfreude, or are there circumstances that mitigate this emotion when they fall from grace?…”
mentioning
confidence: 99%
“…Research on schadenfreude has shown this malicious joy to be evoked by the downfall of high achievers, especially when they are envied or resented (Feather & Sherman, 2002;Smith et al, 1996;Van Dijk, Ouwerkerk, Goslinga, Nieweg, & Gallucci, 2006). But are high achievers always an easy prey for schadenfreude, or are there circumstances that mitigate this emotion when they fall from grace?…”
mentioning
confidence: 99%
“…These empirical studies showed that schadenfreude is more likely to occur when misfortunes happen to high achievers, tall poppies (Feather, 1993(Feather, , 1994, or people who are envied (Smith et al, 1996;Van Dijk, Ouwerkerk, Goslinga, Nieweg, & Gallucci, 2006), disliked (Hareli & Weiner, 2002;Van Dijk et al, 2006), or resented (Feather & Sherman, 2002).…”
mentioning
confidence: 99%
“…In this sense, envy cannot have positive characteristics, and if it has, it is not envy. Miceli and Castelfranchi (2007) van Dijk, Ouwerkerk, Goslinga, Nieweg, and Gallucci (2006) found that envy predicted schadenfreude beyond hostile feelings, indicating that the conflicting results of earlier studies cannot depend of the use of hostile feelings in the assessment of envy. Both envy and hostile feelings had their own individual contribution to the experience of schadenfreude.…”
Section: The Difference Between Envy Jealousy and Schadenfreudementioning
confidence: 91%
“…Feather and Sherman (2002), Hareli and Weiner (2002) and Leach and Spears (2008) failed to find a relation between envy and schadenfreude. Other researchers found a positive relation between the two concepts (e.g., Brigham et al 1997;van Dijk et al, 2006). Feather and Sherman suggested that resentment about another's undeserved success rather than envy that predicted schadenfreude.…”
Section: The Difference Between Envy Jealousy and Schadenfreudementioning
confidence: 98%